2015
DOI: 10.1371/journal.pone.0134949
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Glycoengineering of IgG1 and Its Effect on Fc Receptor Binding and ADCC Activity

Abstract: The importance and effect of Fc glycosylation of monoclonal antibodies with regard to biological activity is widely discussed and has been investigated in numerous studies. Fc glycosylation of monoclonal antibodies from current production systems is subject to batch-to-batch variability. If there are glycosylation changes between different batches, these changes are observed not only for one but multiple glycan species. Therefore, studying the effect of distinct Fc glycan species such as galactosylated and sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
202
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(224 citation statements)
references
References 36 publications
22
202
0
Order By: Relevance
“…It was suggested that the alteration of composition ratios was probably caused by conversion from one type of carbohydrate chain to another in the plasma. Previous studies demonstrated that activities of several glycohydrolases of lysosomal origin, such as β-galacotosidase, β-glucosidase and α-fucosidase, maintained even in plasma [32, 33]. In addition, Gmeiner B et al reported that activities of glycosyltransferases such as galactosyltransferase were detected in several cell lines and their culture media [34].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the alteration of composition ratios was probably caused by conversion from one type of carbohydrate chain to another in the plasma. Previous studies demonstrated that activities of several glycohydrolases of lysosomal origin, such as β-galacotosidase, β-glucosidase and α-fucosidase, maintained even in plasma [32, 33]. In addition, Gmeiner B et al reported that activities of glycosyltransferases such as galactosyltransferase were detected in several cell lines and their culture media [34].…”
Section: Discussionmentioning
confidence: 99%
“…, 67-69 By carrying out enzymatic hyper-galactosylation across four batches of monoclonal antibodies produced from standard manufacturing processes in CHO cells, Thomann et al. demonstrated that hyper-galactosylation of antibody samples consistently leads to improvement in FcγRIIIa binding and ADCC 68 .…”
Section: Fc Galactosylation and Sialylation Also Modulate Igg1 Interamentioning
confidence: 99%
“…Eventually, affinity chromatography might be extended to other Fc-receptors, with the knowledge gained from development of the FcRn methods to cover other complex interaction models. Such prototypes have already been tested in the past [39] and will be developed further in the future. Nevertheless, orthogonal methods and in vivo data will have to continuously challenge these analytical methods but also have the potential to drive their development.…”
Section: Future Perspectivementioning
confidence: 99%